The Development of Kant’s Theory of Moral Feeling - Zhouhuang, Zhengmi (Con-Textos Kantianos. International Journal of Philosophy, 2017)
Kant’s critical theory on moral feeling can be divided into two stages: early and late. In the early stage, Kant was committed to accepting and transforming the traditional concept of moral feeling, while in the later stage he turned to developing his own unique theory on the topic. His beliefs about moral feeling changed between these two stages, both regarding the basic meaning of moral feeling (from intuitive empirical feelings to a priori feelings based on rationality) and the function of moral feeling in moral philosophy (from the basis of moral law to the motivation of moral action). This paper argues that these shifts help clarify the framework of Kant’s moral philosophy and introduce a new dimension to Kant’s definition of feelings and the relationship between sensibility and intellectuality. Namely, sensibility is not only determined by intellectuality but also has its unique initiative. Through acting on the body, intellectuality generates intellectual feelings, which in turn assist humans in realizing their intellectual purpose as a limited rational being.